Modern possibilities of using autologous platelet-rich plasma (PRP) for the correction of age-related skin changes - Chornenka, A. S.; Makurina, G. I.; Siusiuka, V. H.; Shevchenko, A. O.; Чорненька, Альона Сергіївна; Макуріна, Галина Іванівна; Сюсюка, Володимир Григорович; Шевченко, Анна Олександрівна (My University, 2023)
Human life expectancy is constantly increasing, so the search for methods that improve the quality and social adaptation of patients continues. Aging is a set of body changes that affect general homeostasis. Age-related skin changes are one of the visible aspects of chronological aging combined with the influence of modifying factors (ultraviolet radiation, environmental pollution, stress, smoking, diet, cosmetic products, etc.) [1, 2].
Keywords: тези доповідей